Development of Critical Infrastructures in Germany: Out of the Shadow - Alexander Kotov (Научно-аналитический вестник Института Европы РАН, 2021)
The coronavirus epidemic has redefined the importance of critical infrastructure for economic development. In Germany, formally, the Strategy for the Protection of Critical Infrastructure has been in effect since 2009, but it was 2020 that became a turning point. The article analyzes the reflection of the concept of critical infrastructure in various sectoral strategies of Germany. The paper demonstrates that the Coronavirus has become a catalyst for the folding of new regulation in the information and communication industry. It is emphasized that ensuring the protection of critical investments opens up opportunities for the further development of digital infrastructure. The author concludes that the development of critical infrastructures and the achievement of technological sovereignty in key areas will be one of the priorities of the Germany`s economic policy. Most likely, an active proposal of new initiatives by Germany and stimulation of further cooperation of European states with each other in this area is expected to ensure investment control in the political and economic space of the EU.